2014
DOI: 10.1039/c3fo60677e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the metabolic effects of hydroxytyrosol and its lipophilic derivatives (hydroxytyrosyl acetate and ethyl hydroxytyrosyl ether) in hypercholesterolemic rats

Abstract: Hydroxytyrosol (HT), a virgin olive oil phenolic phytochemical with proven health benefits, has been used to generate new lipophilic antioxidants to preserve fats and oils against autoxidation. The aim of this work is to comparatively evaluate the physiological effects of HT and its lipophilic derivatives, hydroxytyrosyl acetate (HT-Ac) and ethyl hydroxytyrosyl ether (HT-Et), in high-cholesterol fed animals. Male Wistar rats (n ¼ 8)were fed a standard diet (C group), a cholesterol-rich diet (Chol group) or a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 41 publications
7
42
1
Order By: Relevance
“…Our transcriptomic analysis confirms previous results from our group [13] and those of other groups [23][24][25] pointing towards physiological effects of HT on oxidation-reduction processes. We now provide evidence that, in the small intestine, long-term HT supplementation also influences these pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our transcriptomic analysis confirms previous results from our group [13] and those of other groups [23][24][25] pointing towards physiological effects of HT on oxidation-reduction processes. We now provide evidence that, in the small intestine, long-term HT supplementation also influences these pathways.…”
Section: Discussionsupporting
confidence: 93%
“…We now found that cholesterol concentrations were not modified by HT supplementation, which is also reflected by the plasma lipoprotein profile. Other studies also found no changes in plasma cholesterol after HT supplementation [24]. We also evaluated tissue cholesterol levels in both the intestine and liver and found no significant changes.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, phenols stripped-EVOO resulted in the same serum lipid profile as EVOO. Our results are not in agreement with other studies, where a HCD was co-administered with phenolic compounds in rats (Jemai et al, 2008;Tabernero et al, 2014). However, in these studies, phenolic compounds were evaluated individually and not as native food components.…”
Section: Discussioncontrasting
confidence: 81%
“…Other studies on cholesterol-fed rats supplemented with phenolics are not in agreement with this finding [36,37]; yet, in these studies isolated phenolic compounds were supplied in the absence of other oil components. Heart tissue has been affected by hyperlipidemia; oxidation was indicated by increase in MDA in cholesterol-fed rats and inflammation by increase in TNF-α, in compliance with other studies [38].…”
Section: Discussionmentioning
confidence: 43%